Sex‐related differences and effects of short and long trail running races on resting muscle‐tendon mechanical properties. (6th July 2022) - Fouré, Alexandre; Besson, Thibault; Stauffer, Emeric; Skinner, Sarah C.; Bouvier, Jérémie; Féasson, Léonard; Connes, Philippe; Hautier, Christophe A.; Millet, Guillaume Y.
Abstract : The purpose of the study was to assess sex‐related differences in resting mechanical properties and adaptations of skeletal muscles and tendons in response to trail running races of different distances using multi‐site shear wave elastography assessments of the lower limb, force capacity and blood analyses. Sex differences in resting mechanical properties of knee extensor and plantar flexor muscles and tendons were characterized by shear wave velocity (SWV) measurements in healthy males ( N  = 42) and females ( N  = 25) trained in long‐distance running. Effects of running distance on muscle and tendon properties were assessed in short (<60 km, N  = 23) vs. long (>100 km, N  = 26) distance races. Changes in isometric maximal voluntary contraction torque, serum C‐reactive protein and creatine kinase activity were also quantified after running races. Higher SWV of relaxed triceps surae muscle was detected in females as compared to males before running races (+4.8%, p  = 0.006), but the significant increases in triceps surae muscle group (+7.0%, p  = 0.001) and patellar tendon SWV (+15.4%, p  = 0.001) after short‐distance races were independent of sex. A significant decrease in triceps surae muscle SWV was found after long‐distance races in the whole experimental population (−3.1%, p  = 0.049). Post‐races increase in C‐reactive protein and creatine kinase activity were significantly correlated to the relative decreases in triceps surae and quadriceps femoris skeletal muscle SWV ( ρ  = −0.56, p  = 0.001 and ρ  = −0.51, p  = 0.001, respectively). Resting mechanical properties of muscles and tendons are affected by sex, and adaptations to trail races are related to running distance. Exercise‐induced changes in resting skeletal muscle mechanical properties are associated with enhanced indirect markers of inflammation and muscle damage.